GABAA Alpha 2,3 Modulation Improves Select Phenotypes in a Mouse Model of Fragile X Syndrome - Schaefer, Tori L.; Ashworth, Amy A.; Tiwari, Durgesh; Tomasek, Madison P.; Parkins, Emma V.; White, Angela R.; Snider, Andrew; Davenport, Matthew H.; Grainger, Lindsay M.; Becker, Robert A.; Robinson, Chandler K.; Mukherjee, Rishav; et al. (Frontiers in Psychiatry, 2021)
Fragile X syndrome (FXS) is the most common cause of inherited intellectual disability. FXS is caused by functional loss of the Fragile X Protein (FXP), also known as Fragile X Mental Retardation Protein (FMRP). In humans and animal models, loss of FXP leads to sensory hypersensitivity, increased susceptibility to seizures and cortical hyperactivity. Several components of the GABAergic system, the major inhibitory system in the brain, are dysregulated in FXS, and thus modulation of GABAergic transmission was suggested and tested as a treatment strategy. However, so far, clinical trials using broad spectrum GABA(A) or GABA(B) receptor-specific agonists have not yielded broad improvement of FXS phenotypes in humans. Here, we tested a more selective strategy in Fmr1 knockout (KO) mice using the experimental drug BAER-101, which is a selective GABA(A) alpha2/alpha3 agonist. Our results suggest that BAER-101 reduces hyperexcitability of cortical circuits, partially corrects increased frequency-specific baseline cortical EEG power, reduces susceptibility to audiogenic seizures and improves novel object memory. Other Fmr1 KO-specific phenotypes were not improved by the drug, such as increased hippocampal dendritic spine density, open field activity and marble burying. Overall, this work shows that BAER-101 improves select phenotypes in Fmr1 KO mice and encourages further studies into the efficacy of GABA(A)-receptor subunit-selective agonists for the treatment of FXS.